2004
DOI: 10.1158/1078-0432.ccr-03-0679
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Glutathione S -Transferase P1-1 as a Prognostic Factor in Patients with Advanced Non-Hodgkin’s Lymphoma (Stages III and IV)

Abstract: Purpose: This study aims to investigate whether the plasma level of glutathione S-transferase P1-1 (GSTP1-1), which is a phase II detoxifying enzyme known to be a resistance factor for anticancer drugs, could be a prognostic factor of de novo non-Hodgkin lymphoma (NHL) in clinical stages (CSs) III and IV.Experimental Design: Study population consisted of 80 NHL patients with no prior treatment: 12 patients were at CS I, 14 at CS II, 25 at CS III, and 29 at CS IV. All 54 patients at CS III or CS IV were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
1
15
0
1
Order By: Relevance
“…In neoplasms other than lung cancer, the overexpression of GST-pi and P-gp has been associated with decreased treatment response and survival. [16][17][18] In patients with lung cancer, the link between GST-pi and P-gp expression and tumor chemosensitivity has been documented by several trials in advanced NSCLC. 4,5,[7][8][9][10][11] In this regard, Hida et al observed that pretreatment serum GST-pi levels may be a useful parameter for predicting therapeutic response to combination chemotherapy regimens that include platinum compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In neoplasms other than lung cancer, the overexpression of GST-pi and P-gp has been associated with decreased treatment response and survival. [16][17][18] In patients with lung cancer, the link between GST-pi and P-gp expression and tumor chemosensitivity has been documented by several trials in advanced NSCLC. 4,5,[7][8][9][10][11] In this regard, Hida et al observed that pretreatment serum GST-pi levels may be a useful parameter for predicting therapeutic response to combination chemotherapy regimens that include platinum compounds.…”
Section: Discussionmentioning
confidence: 99%
“…GST enzymes have a broad substrate specificity [34] that includes substances with known mutagenic properties. Elevated serum GST p has been exploited as a serum tumor marker for gastrointestinal cancer [16] and more recently for non-Hodgkin lymphoma [35] as a method of predicting sensitivity to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2011) confirmed that GSTp in comparison to MRP1 is the much more important mediator to predict the intrinsic resistance to cisplatin. The multivariate analysis showed that there was a significant correlation between increased plasma GSTp concentration and lower overall survival or progression-free survival Katahira et al (2004). This negative prognostic influence was strongest in stage I and II squamous cell lung carcinomas.…”
Section: Discussionmentioning
confidence: 91%